COMPETENCY ANALYSIS, INTERNAL CONTROL SYSTEM AND VILLAGE GOVERNMENT ACCOUNTABILITY IN MANAGING VILLAGE FUND ALLOCATION : (Case Study in Simanindo District) - Saragih, Joana L.; Napitu, Yuni Tresa (UNIKA Santo Thomas, 2023)
Purpose of this research was to determine the needs of the village government in managing village fund allocations, to find out how the village government's internal control system was in managing village fund allocations and to analyze village government accountability in managing village fund allocations. The population in this study are villages whose realization of village fund allocations is less than 95% during 2019-2021, namely Maduma Village and Simanindo Village. The sample is part of the population, where the sample in this study is the village government in Maduma Village and Simanindo Village. Data collection techniques in this study were carried out by interview techniques. The data analysis technique used by researchers in this study is descriptive analysis method, with this method data and information are needed to support research. Based on the results of the research conducted, it can be seen that the village apparatus in Maduma Village and Simanindo Village have competence both in terms of knowledge, skills and attitudes. In managing the Allocation of Village Funds, the Maduma Village Government and Simanindo Village have implemented an internal control system in accordance with PP number 60 year 2008. Village Government Accountability in managing Village Fund Allocations in Maduma Village and Simanindo Village at the planning stage. implementation, administration and accountability have been said to be accountable and in accordance with Permendagri number 20 year 2018.